AltitudeOmics: Spontaneous Baroreflex Sensitivity During Acclimatization to 5,260 m: A Comparison of Methods - Bourdillon, Nicolas; Yazdani, Sasan; Vesin, Jean-Marc; Subudhi, Andrew W.; Lovering, Andrew T.; Roach, Robert C.; Kayser, Bengt (Frontiers in Physiology, 2019)
Introduction: Baroreflex sensitivity (BRS) is essential to ensure rapid adjustment to variations in blood pressure (BP). Spontaneous baroreflex function can be assessed using continuous recordings of blood pressure. The goal of this study was to identify the most reliable method for BRS quantification across rest and exercise, in normoxia, hypoxia, hypocapnia and hypercapnia, by comparing the sequence method, Bernardi’s method (BER), the frequency method and the transfer function method. Methods: Using intra-radial artery BP in young healthy participants, BRS was calculated and compared using the four methods in normoxia, acute and chronic hypoxia (terrestrial altitude of 5,260 m) in hypocapnia (hyperventilation), hypercapnia (rebreathing) and during ramp exercise to exhaustion. Results: The sequence and BER methods for BRS estimation showed good agreement during the resting and exercise protocols, whilst the ultra- and very-low frequency bands of the frequency and transfer function methods were more discrepant. Removing respiratory frequency from the blood pressure traces affected primarily the sequence and BER methods and occasionally the frequency and transfer function methods. Discussion/Conclusion: The sequence and BER methods contained more respiratory related information than the frequency and transfer function methods, indicating that the former two methods predominantly rely on respiratory effects on BRS. BER method is recommended because it is the easiest to compute. Even though it tends to overestimate BRS compared to the sequence method, it is consistent with the other methods, and its interquartile range is the smallest.